Trade Relationship Between Turkey and South Africa a Brief Overview of The Last 20 Years - Yetkin, Ahmet Murat (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
In the 2000s, a single political party became able to manage Turkey alone for the first time in the country’s history. By ensuring internal stability, Turkey started to build and improve its relationships with foreign countries. In this manner, Turkey decided to look for ways to strengthen its relations with the African continent and especially with South Africa.